Impact of the Financial Markets Development on Capital Structure of Firms Listed on Ho Chi Minh Stock Exchange - Tai, Le Minh (International Journal of Economics and Financial Issues, 2017)
This study test the impact of financial markets development on capital structure of firms listed on Ho Chi Minh stock exchange (HOSE). Base on the financial data of 116 firms listed on HOSE, in the period from 2009 to 2015 and GLS regression method, this study shows that market capitalization is positive relationship with debt rate in capital structure, volume of shares traded is negative effect to debt rate in capital structure. Size of the Vietnamese commercial banking system and credit growth are negative relationship with debt rate in capital structure. Meanwhile, interest rates of commercial banks is not statistical significance. Keywords: Financial markets, capital structure JEL Classifications: G10, G21, G32